2023
DOI: 10.3390/ma16062233
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of Hexavalent Chromium in Aqueous Solutions Using a Magnetic Silica-Coated Amino-Modified Glycidyl Methacrylate Polymer Nanocomposite

Abstract: A new magnetic amino-functionalized polymeric sorbent based on glycidyl methacrylate was synthesized and used in the separation of chromium Cr(VI) oxyanions sorption from aqueous solutions in a static batch system. The kinetic and isothermal parameters of the sorption process were determined. The experimental data were best fitted by a pseudo-second-order model with R2 = 0.994 and χ2 = 0.004. The sorption process of Cr(VI) removal by amino-functionalized sorbent was controlled by both intraparticle diffusion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Brief analyses of the structural parameters for the [AuCl 4 ] − ion with the structure of the [AuCl 4 ] − anion (Figure S1) are given in the Supplementary Materials. The intra-particle plots (Figure 5b) show three distinct stages: a liquid film diffusion stage, an intra-particle diffusion stage, and a final equilibrium stage [37]. According to the obtained results, the intra-particle plots were linear and deviated from the origin, suggesting that the adsorption of Au onto pGME-en was controlled by both liquid film and intra-particle diffusion.…”
Section: Adsorption Kineticsmentioning
confidence: 64%
See 2 more Smart Citations
“…Brief analyses of the structural parameters for the [AuCl 4 ] − ion with the structure of the [AuCl 4 ] − anion (Figure S1) are given in the Supplementary Materials. The intra-particle plots (Figure 5b) show three distinct stages: a liquid film diffusion stage, an intra-particle diffusion stage, and a final equilibrium stage [37]. According to the obtained results, the intra-particle plots were linear and deviated from the origin, suggesting that the adsorption of Au onto pGME-en was controlled by both liquid film and intra-particle diffusion.…”
Section: Adsorption Kineticsmentioning
confidence: 64%
“…In addition, epoxy ring vibrations at 1256, 910, and 847 cm −1 , such as stretching carbonyl vibrations at 1722 cm −1 peaks, were found [37,38]. Compared with the pGME spectrum, the appearance of new absorption bands was observed at 1656, 1561 (N-H bending vibrations), and 754 cm −1 (N-H wagging vibrations), as well as broad bands assigned to the -OH and to the N-H stretching vibrations, with a maximum at ~3400 cm −1 [37,39]. Also, a decreasing intensity of characteristic epoxy vibration peaks was observed.…”
Section: Adsorbent Characterizationmentioning
confidence: 97%
See 1 more Smart Citation
“…The method was validated by analyzing several CRM-Tibet soil, strawberry leaves and applying it to Cr speciation in food, biological, and soil samples. A new sorbent was prepared following a relatively complicated synthesis procedure: Macroporous magnetic poly (glycidyl methacrylate-co-ethylene glycol dimethacrylate) is obtained by in situ suspension copolymerization in the presence of Fe 3 O 4 nanoparticles coated with a silanization agent 3-aminopropyltriethoxysilane (APTES) and further functionalized with diethylenetriamine with the main aim of selective removal of Cr(VI) [ 78 ]. The results indicated that Cr(VI) oxyanions that bind to the sorption sites can be converted on the surface of the sorbent to a less harmful form of Cr(III) due to the sorbent’s chemical composition.…”
Section: Polymeric Materials For Solid-phase Extractionmentioning
confidence: 99%
“…Among these methods, adsorption effectively concentrates Cr(VI) by two main forces, i.e., electrostatic interactions and coordination interactions, which are recognized as easy, fast, and highly efficient environmental protection techniques without secondary waste [ 18 , 19 , 20 , 21 , 22 , 23 ]. A wide variety of adsorption materials for the removal of Cr(VI) in wastewater have been reported, such as metal hydroxides [ 24 ], silica-based materials [ 25 , 26 , 27 ], biochar [ 28 ], activated carbon [ 29 , 30 , 31 ], various types of clay minerals [ 32 , 33 ], chitin and chitosan [ 34 , 35 , 36 ], zeolites [ 37 ], graphene oxide [ 38 , 39 , 40 ], amino-functionalized silica [ 41 ], amino-functionalized magnetic polymers [ 42 ] and metal–organic frameworks (MOFs) [ 43 , 44 , 45 , 46 ]. Among these adsorption materials, MOFs are a novel class of crystalline porous material with periodic network structure formed by the interconnection of inorganic metal centers (metal ions or metal clusters) and bridging organic ligands through self-assembly [ 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%